Apobec3A Deamination Functions Are Involved in Antagonizing Efficient Human Adenovirus Replication and Gene Expression - Lilian Göttig; Christina Weiß; Miona Stubbe; Lisa Hanrieder; Samuel Hofmann; Alessandro Grodziecki; Daniela Stadler; Arnaud Carpentier; Ulrike Protzer; Sabrina Schreiner (mBio, 2023)
ABSTRACT Apobec3A is involved in the antiviral host defense, targeting nuclear DNA, introducing point mutations, and thereby activating DNA damage response (DDR). Here, we found a significant upregulation of Apobec3A during HAdV infection, including Apobec3A protein stabilization mediated by the viral proteins E1B-55K and E4orf6, which subsequently limited HAdV replication and most likely involved a deaminase-dependent mechanism. The transient silencing of Apobec3A enhanced adenoviral replication. HAdV triggered Apobec3A dimer formation and enhanced activity to repress the virus. Apobec3A decreased E2A SUMOylation and interfered with viral replication centers. A comparative sequence analysis revealed that HAdV types A, C, and F may have evolved a strategy to escape Apobec3A-mediated deamination via reduced frequencies of TC dinucleotides within the viral genome. Although viral components induce major changes within infected cells to support lytic life cycles, our findings demonstrate that host Apobec3A-mediated restriction limits virus replication, albeit that HAdV may have evolved to escape this restriction. This allows for novel insights into the HAdV/host-cell interplay, which broaden the current view of how a host cell can limit HAdV infection. IMPORTANCE Our data provide a novel conceptual insight into the virus/host-cell interplay, changing the current view of how a host-cell can defeat a virus infection. Thus, our study reveals a novel and general impact of cellular Apobec3A on the intervention of human adenovirus (HAdV) gene expression and replication by improving the host antiviral defense mechanisms, thereby providing a novel basis for innovative antiviral strategies in future therapeutic settings. Ongoing investigations of the cellular pathways that are modulated by HAdV are of great interest, particularly since adenovirus-based vectors actually serve as COVID vaccine vectors and also frequently serve as tools in human gene therapy and oncolytic treatment options. HAdV constitute an ideal model system by which to analyze the transforming capabilities of DNA tumor viruses as well as the underlying molecular principles of virus-induced and cellular tumorigenesis.